Promoting Engineering Education Through Visible Learning and Formative Assessment Strategies - Velani, Mihir N. (Journal of Engineering Education Transformations, 2021)
The assessment and teaching strategies are chief indicators of comprehended learning in the field of education. They are the critical moves in the learning process, specifically when related to engineering and science. The mediocre content delivery and inferior assessment affect several educational spheres, such as faculty development, student scores, placement, and life-long experience. These two factors considerably regulate the programspecific outcomes (PSOs) and course outcomes (COs). The present work focuses on analyzing the effects of learning and assessment methods to achieve the designated PSOs and COs through visible learning. The analysis has been carried out with Hattie’s effect size that influences the program and course achievement. The process was monitored for two subjects offered to the limited population of undergraduate students of Electrical Engineering. The statistics have been derived in the effect size affected by the source of influence, aspect, and factor. Further, the possibilities of incorporating formative evaluation and visible learning in Indian engineering education is framed in the discussion.